IMPACT OF BUSINESS ENVIRONMENT ON ORGANIZATION PERFORMANCE IN NIGERIAA STUDY OF UNION BANK OF NIGERIA - Eruemegbe, Gloria Obiageli (European Scientific Journal, ESJ, 2015)
The study seeks to unravel the factors that affect construction workers’ motivation and the corresponding effect of the identified motivational factors on workers’ performance and overall productivity. To answer research question and test formulated hypotheses, the study relied on questionnaire to generate relevant data out of 39 questionnaires administered on officers in Union Bank of Nigeria, Lagos, only 20 were properly completed and returned. This gave an effective response rate of 51%. The survey revealed that, among the top ten critical factors (i.e. teamwork, work based on contract, supervision based on leadership by example and provision of equipment) had great effect on motivation as well as impact on productivity. More so communication, love and belongingness, opportunity to undertake challenging task, identification with goal and overtime were among the critical factors.